Training workshop report on good agricultural practices for the production and conservation of seed potato in the West, Adamawa, and Northwest regions. Workshop report. - Fornkwa, V.; Harahagazwe, D.; Adamu, I.; Tiozang, E.; Apan, A.; Ngwa, L.; Djatsa, E.; Woulbe, C.; Mafouo, H.; Anagho, R. (International Potato Center, 2021)
The International Potato Center (CIP), in collaboration with the Green Innovation Centers for the Food and Agriculture sector (ProCISA), the Ministry of Agriculture and Rural Development (MINADER), and the Institute of Agricultural Research for Development (IRAD), organized and facilitated training workshops for seed growers on Good Agricultural Practices (GAPs) for the production and conservation of seed potato. The workshops that took place in ADYS hotel in Dschang on 26 – 27 April 2021, TRANSCAM hotel in Ngaoundere on 5 – 7 May 2021, ADYS Hotel in Dschang on 9 -11 August 2021, brought together active and potential seed growers from the West, Adamawa, and Northwest regions, respectively. Seed growers from Lebialem division (South-West region) were also invited to join the Northwest cohort. The aim of the workshops was to share the knowledge with participants on Good Agricultural Practices for the production and conservation of seed potato. The workshops were moderated by the regional MINADER – ProCISA Focal Points and facilitated by CIP and IRAD researchers, as well as representatives of the Directorate of Regulation and Quality Control of Agricultural Inputs and Products (DRCQ). In the Adamawa, a translator was brought on board to translate all the presentations and questions and answersinto the local language Fulfulde, given that participants could neither express themselves in the French language nor understand it. This was an opportunity for participants in the three regions to (i) identify the constraints they face in seed production and conservation, (ii) know about the standard seed and variety schemes, (iii) learn GAPs for the production and conservation of seed potato, (iv) and identify their individual needs and define individual action plans to improve their agribusiness in seed potato. The theoretical sessions were conducted in a participatory manner combining PowerPoint presentations, questions, and answers as well as discussions and sharing of personal experiences. Field demonstrations were equally carried out during which participants were drilled on the identification of pests and diseases, positive and negative selection, dehaulming, phytosanitary treatment, and the proper handling of phytosanitary products, amongst others. Participants in the workshops were either active seed potato growers or those aspiring to venture into seed potato production. In the West region, fifteen (15) participants attended, of whom only one (01) was a woman. In the Adamawa region, eighteen (18) participants took part, of whom six (06) were women. For the Northwest region and Lebialem division, twenty-four (24) participants attended the training, of whom six (06) were women. At the end of the workshops, trainees were satisfied with the knowledge acquired and expressed the need to be accompanied for bettering the quality and quantity of their seed in their respective regions and divisions.